2023
DOI: 10.3390/en16031215
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Heated Turbulent Flow in a Channel with Pin Fins

Abstract: Large-eddy simulations (LES) were performed to study the turbulent flow in a channel of height H with a staggered array of pin fins with diameter D = H/2 as a function of heating loads that are relevant to the cooling of turbine blades and vanes. The following three heating loads were investigated—wall-to-coolant temperatures of Tw/Tc = 1.01, 2.0, and 4.0 - where the Reynolds number at the channel inlet was 10,000 and the back pressure at the channel outlet was 1 bar. For the LES, two different subgrid-scale m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Cooling efficiency is essential in the region along the edge of the turbine blades and vanes. Lee et al [29] applied large-eddy simulations to study turbulent flow in a channel of a certain height with a staggered array of pin fins with an appropriate diameter as a function of the heating loads that are relevant for the cooling of turbine blades and vanes. The results of the simulations were validated on the basis of data obtained from direct numerical simulation and experiments.…”
Section: Review Of New Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooling efficiency is essential in the region along the edge of the turbine blades and vanes. Lee et al [29] applied large-eddy simulations to study turbulent flow in a channel of a certain height with a staggered array of pin fins with an appropriate diameter as a function of the heating loads that are relevant for the cooling of turbine blades and vanes. The results of the simulations were validated on the basis of data obtained from direct numerical simulation and experiments.…”
Section: Review Of New Advancesmentioning
confidence: 99%
“…The results of the simulations were validated on the basis of data obtained from direct numerical simulation and experiments. The authors concluded that there are significant changes in the turbulent flow structure caused by heating loads, creating wall jets next to all heated surfaces [29].…”
Section: Review Of New Advancesmentioning
confidence: 99%
“…Due to the high pursuit of engine thermal efficiency and power output, the hot gas temperature has now exceeded 1800 • C, making the efficient and reliable cooling of turbine blades a severe challenge that requires an optimal cooling solution. To further increase overall cooling effectiveness, several advanced cooling technologies have been proposed and studied in recent years, including the optimization of cooling geometry parameters, the improvement of complicated cooling strategies, and the development of new cooling approaches based on innovation cooling theories [2][3][4]. Among these, the tree-like branching microchannel cooling technology, which possesses excellent overall heat transfer performance, has attracted the attention of researchers for blade cooling in gas turbines.…”
Section: Introductionmentioning
confidence: 99%